The Problem of Stage Preparation of the Future Primary School Teachers in Domestic Pedagogics (End of the XVIII – Beginning of the XX Century - Shkvyr, Oksana (Pedagogical Discourse, 2012)
The results of research of the problem of stage preparation of the future primary school teachers in domestic pedagogics (end of the XVIII – beginning of the XX century) have been elucidated in the article.